CELLKINE CLINICAL TRIAL: FIRST REPORT FROM A PHASE I TRIAL OF ALLOGENEIC BONE MARROW-DERIVED MESENCHYMAL STEM CELLS IN SUBJECTS WITH PAINFUL LUMBAR FACET JOINT ARTHROPATHY - Yan, D.; Zubair, A.; Osborne, M.; Rosado, R. Pagan; Stone, J.A.; Lehman, V.; Durand, N.; Kubrova, E.; Wang, Z.; Witter, D.M.; Baer, M.M.; Ponce, G.C.; et al. (Cytotherapy (Oxford, England), 2024)
Lumbar facet joint arthropathy (LFJA) is a leading cause of low back pain (LBP); however, current treatment options lack the ability to provide long-term benefits. Bone marrow-derived mesenchymal stem cells (BM-MSCs) are of particular interest owing to their potential immunomodulatory and trophic impacts offer promise, potentially targeting underlying degenerative processes in LFJA. This case report describes the initial outcomes of the first patient enrolled in a Phase I clinical trial evaluating allogeneic culture-expanded BM-MSCs for the treatment of painful LFJA. Methods: Following enrollment in our IRB approved protocol, symptomatic LFJA was verified through bilateral L4-L5 medial branch blocks, yielding positive outcomes of over 75% pain alleviation. Two 1mL syringes each containing 10 million passage 3 BM-MSCs were prepared in the cGMP facility and then administered to her bilateral L4-L5 lumbar facet joints. BM-MSCs were isolated from a healthy 28-year-old female donor, culture-expanded, cryopreserved and stored in vapor phase liquid nitrogen (less than -150oC). Quality control testing was performed on the final cryopreserved cell product prior to the release. The patient underwent standardized follow-ups, including clinical examinations, functional and imaging assessments for two years as reflected in the Patient-Reported Outcomes Measurement Information System - Computer Adaptive Testing (PROMIS-CAT), Work Functional Status & Narcotic Pain Medication Use questionnaires and sequential MRI evaluation up to 24 months. The patient tolerated the procedure well and did not experience any drug-related adverse events (SAEs) during the study period. Pain (PROMIS-CAT Pain Interference), function of the spine (PROMIS-CAT Physical Function), and work functional status were improved at multiple follow-ups. This patient also reported improvements in mental (PROMIS-CAT Anxiety, Depression, Sleep Disturbance and Fatigue) and social health (PROMIS-CAT Ability to Participate Social Roles and Activities). Moreover, this patient had a significant decrease in the grade of facet synovitis at one-year follow-up MRI evaluation. This case report implies a positive outlook regarding the safety and feasibility of administering intra-articular allogeneic BM-MSCs, along with potential therapeutic advantages for pain management and functional activities. As the trial progresses, our understanding will continue to expand.